HUBUNGAN POLA ASUH ORANG TUA DENGAN PENYESUAIAN DIRI PESERTA DIDIK DI SMA N 16 PADANG - Utama, Debi Putra; Arief, Asmaiwaty; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Family is the main principle in forming childrenâs act. Walking on their live, children need their parents support like parenting and support to a better live. In this case, to form well studentsâ self adjustment in school, it is also need well parenting of parents at home. Because of that, this research was conducted to discover how the parentsâ parenting was able to build up studentsâ self adjustment. This research was designed by descriptive correlation. The population was students of XI class in Senior High School 16 Padang. The sampling was taken by using random sampling, which the total number of sampling was 70 students. The instrument of the research was questionnaire. To analyze the data, the researcher used pattern of product moment correlation coefficient, which issued by Karl Pearson, in form of windows release 17.0 program, called statistical product and service solution. Generally, the result of research showed that there was a significant relationship between parentsâ parenting with studentsâ self adjustment in school. Thus, as the conclusion, it can be said that the parentsâ parenting and studentsâ self adjustment were on powerful level of significance